2013
DOI: 10.1136/bjophthalmol-2013-303084
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up for efficacy and safety of treatment of retinitis pigmentosa with valproic acid

Abstract: VPA plays a complex role in patients with pigmentary retinal dystrophies and may be associated with VA and field decline as well as adverse side effects. Physicians should use caution with using VPA for pigmentary retinal dystrophies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 16 publications
0
28
0
1
Order By: Relevance
“…A preliminary study with valproic acid had suggested therapeutic benefit in some patients with RP (Clemson et al 2011). However, the long-term follow-up of 31 RP patients revealed possible declines in visual acuity and field, suggesting caution in the use of this drug to treat pigmentary retinal dystrophies (Bhalla et al 2013). Efficacy and safety of oral valproic acid for RP is under clinical investigation (http://ClinicalTrials.gov.…”
Section: Alternative Pharmacological Approachesmentioning
confidence: 99%
“…A preliminary study with valproic acid had suggested therapeutic benefit in some patients with RP (Clemson et al 2011). However, the long-term follow-up of 31 RP patients revealed possible declines in visual acuity and field, suggesting caution in the use of this drug to treat pigmentary retinal dystrophies (Bhalla et al 2013). Efficacy and safety of oral valproic acid for RP is under clinical investigation (http://ClinicalTrials.gov.…”
Section: Alternative Pharmacological Approachesmentioning
confidence: 99%
“…Controversial effects on the actions of VPA on small groups of RP patients (Sisk, 2012) indicated that only dominant mutations could possibly benefit from the treatment with this drug. An additional study on a small group of RP patients receiving short-term (3 months) administration of VPA lead to the conclusion that this substance does improve the vision and visual field (Shanmugam et al, 2012), but results of a clinical trial published in 2013 (Bhalla et al, 2013) concluded that long-term VPA treatment of RP may be associated with visual acuity and visual field decline and with other adverse side effects. Finally, a very recent clinical study indicates that VPA has positive effects on the visual functions of typical RP patients (Kumar et al, 2014).…”
Section: Valproic Acid (Vpa)mentioning
confidence: 96%
“…Nie zaobserwowali działań niepożądanych. Inni autorzy, oceniając retrospektywne wyniki pacjentów z RP przyjmujących kwas walproinowy, stwierdzili pogarszanie się ostrości wzroku, zawężanie pola widzenia oraz występo-wanie działań niepożądanych [32].…”
Section: Suplementacja Kwasu Walproinowegounclassified